2001
DOI: 10.1001/archneur.58.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Axonal Damage in the Early Stages of Multiple Sclerosis and Its Relevance to Disability

Abstract: Cerebral axonal damage begins and contributes to disability from the earliest stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
261
2
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 464 publications
(301 citation statements)
references
References 52 publications
28
261
2
10
Order By: Relevance
“…Remyelination becomes less efficient in the later stage of MS in part due to a failure of OPC differentiation (Franklin and ffrench‐Constant, 2008; Kuhlmann et al, 2008; Wolswijk, 1998). Failure of remyelination is a major contributor to the accumulation of axonal and neuronal degeneration that characterizes the progressive stage of the disease in which clinical deficits accumulate over time (Bjartmar et al, 2000; De Stefano et al, 2001). The axonal degeneration observed after toxin‐induced demyelination in mice depleted of OPCs is prevented by the transplantation of exogenous OPCs that restore remyelination capacity (Irvine and Blakemore, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Remyelination becomes less efficient in the later stage of MS in part due to a failure of OPC differentiation (Franklin and ffrench‐Constant, 2008; Kuhlmann et al, 2008; Wolswijk, 1998). Failure of remyelination is a major contributor to the accumulation of axonal and neuronal degeneration that characterizes the progressive stage of the disease in which clinical deficits accumulate over time (Bjartmar et al, 2000; De Stefano et al, 2001). The axonal degeneration observed after toxin‐induced demyelination in mice depleted of OPCs is prevented by the transplantation of exogenous OPCs that restore remyelination capacity (Irvine and Blakemore, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the recent few years, several studies demonstrated the presence of axonal degeneration even in the initial stages of MS. [1][2][3][4] Axonal loss is an irreversible process and is related to permanent disability observed in MS; therefore, the monitoring of axonal loss is important for the follow-up of the disease and the development of a targeted treatment strategy. 2 Retinal cell axons are part of the CNS, and do not have a myelin sheath until they penetrate the lamina cribrosa, thus the investigation of retina might be ideal for visualising the processes of neuroaxonal degeneration and understanding mechanisms of brain tissue damage in multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional 1 H-MRSI scans were obtained using a 90°-180°-180°pulse sequence (TR 2000 ms, TE 272 ms, 32 × 32 phase-encoding steps with 1 signal average per step, and a 250-mm field of view), the effective spatial resolution being about 12 × 12 × 20 mm after k-space filtering. These methods are presented in more detail elsewhere [17,18]. 1 H-MRSI findings: The superimposed grid in each image represents the 1 H-MRSI voxels, and the large, thick, white box represents the 1 H-MRSI volume of interest for that individual.…”
Section: Metabolites Of Interest In Msmentioning
confidence: 99%